Kebijakan Unilateral Penanganan Imigran Ilegal Australia Pasca Pemilihan Umum Australia Tahun 2013 - Rizal, Fakhrul (Global: Jurnal Politik Internasional, 2018)
This article analyzes military policy making made by Australian Government to tackle the issue of illegal immigrants in Australia after the Australian Federal Election in 2013. Some of existing studies on the topic illustrate from the point of view of securitization, that illegal immigrant issues has been securitized and requires the intervention of the Australian army through Operations Sovereign Borders. However, in the context of the 2013 Australian Federal Elections, these earlier studies have not explained the objectives of securitization resulting in an assertive policy in the handling of illegal immigrants. By employing the strands of securitization concept, this paper explains what objectives the securitizing actor wants to achieve from the securitization of illegal immigrant issues in Australia. The findings of this paper indicate that the securitization was aimed at raising the issue of illegal immigrants on the national security agenda due to the emergence of this issue and to gain legitimacy of extraordinary measures to eliminate the threat possesed by illegal immigrants.